An emm5 Group A Streptococcal Outbreak Among Workers in a Factory Manufacturing Telephone Accessories - Chen, Mingliang; Wang, Wenqing; Tu, Lihong; Zheng, Yaxu; Pan, Hao; Wang, Gangyi; Chen, Yanxin; Zhang, Xi; Zhu, Linying; Chen, Jian; Chen, Min (Frontiers in Microbiology, 2017)
Ranked among the top10 infectious causes of death worldwide, group A Streptococcus (GAS) causes small- and large-scale outbreaks, depending on the trigger as transmission of a GAS strain or expansion of predominant clones. In China, GAS infections other than scarlet fever are not notifiable. In Shanghai, an epidemiological investigation was initiated after two successive severe pneumonia cases with one death in a digital factory, from where outbreaks are less widely reported. The investigation was performed using emm typing, pulsed-field gel electrophoresis (PFGE) typing, superantigen profiling, and genome analysis. This enabled characterization of relatedness among the outbreak isolates and identification of the mobile genetic elements present. Among 57 patients with respiratory symptoms investigated in the factory, emm5 GAS strains were isolated from 8 patients. The eight GAS infection cases comprising one fatal severe pneumonia case, six influenza-like illness cases, and one pharyngitis case. Two risk factors were identified: adult with an age of 18-20 years and close contact with a GAS patient or carrier. GAS attack rate was 14.0% (8/57), and GAS carriage rate was probably around 2.7% (14/521) based on surveys in two nearby districts. All the 10 outbreak associated isolates were assigned to emm5 and sequence type ST-99 (emm5/ST-99), harbored superantigen genes speC, speG and smeZ, and were assigned to two similar PFGE patterns (clones). Among the outbreak associated isolates, all carried ermA with resistance to erythromycin and inducible resistance to clindamycin, and eight (80%) carried a tetM gene with resistance to tetracycline. Among the 14 carriage isolates, 12 were emm12/ST-36, and 2 were emm1/ST-28, all with superantigen genes speC, speG, ssa and smeZ. All the carriage isolates harbored ermB and tetM with resistance to erythromycin, clindamycin, and tetracycline. Genome analysis showed the two outbreak clones were closely related and possessed new prophages carrying virulence gene sdc and antibiotic resistance genes of ermA and tetM, which were not found in the emm5 reference strain Manfredo. This is the first report of a GAS outbreak in this type of workplace. The outbreak was caused by two closely-related emm5 clones that differed from the predominant emm types circulating in China.